Mengelola Emosi dan Suasana Hati dalam Membangun Produktivitas dan Kreativitas Pegawai di Lingkungan Kerja - Rifani Yulianti; Oktaviana Eka Fadila; Nadjwa Salsabila; Davina Dwi Sazkia; Zulfa Maulidiya Aeni (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This article discusses the important role of managing emotions and mood in increasing employee productivity and creativity in the work environment. In the midst of increasingly fierce global competition and rapid technological developments, companies are required to maintain optimal performance in order to compete. Employee performance is influenced by a number of elements, including their ability to control emotions and moods. Emotions and mood affect a person's performance, creativity, and productivity in addition to their interactions with other people. Workers who are adept at controlling their emotions, especially emotions of happiness, satisfaction and enthusiasm, will be more involved, innovative and productive at work. On the other hand, negative emotions such as stress, anger and frustration will interfere with motivation and focus, causing emotional dissonance, which results in decreased performance. Therefore, companies must pay more attention to employees' emotional health by providing emotional intelligence training and fostering a positive work atmosphere. Companies can increase productivity and foster sustainable creativity, both of which are very important, by implementing appropriate emotional management strategies in the current era of the industrial revolution.